DIE HARD : LEGACY COLLECTION - Willis, Bruce (Twentieth Century Fox Home Entertainment, 2013)
Bruce Willis stars as John McClane, a New York City police detective in a series of action films where he finds himself fighting a group of terrorists in each installment